Cranial base morphology in different skeletal classes (A cross-sectional lateral cephalometric study) - Bilal I Abd; Fakhri A Ali (College of Dentistry/ University of Baghdad, 2014)
Background: It was stated in scientific literatures that the entire craniofacial complex is influenced by the growth of the cranial base structures. Nevertheless, many times this is not the case, and this point is subject to great controversy so the aim of this study is to evaluate the possible differences in cranial base shape and flexure between different skeletal classes for both genders and to investigate any possible correlation between cranial base variables and other skeletal base variables. Materials and Methods: The sample include 75 lateral cephalometric radiographs of Iraqi adults aged between 18-25 years (39 males, 36 females), collected from patients and undergraduate students in the orthodontic department of College of Dentistry-Baghdad University. The total sample was divided to three major categories depending on ANB angle and dental occlusion into class I control group (12 males, 13 females), class II group (13 males, 12 females) and class III group (14 males, 11 females). Results: The results revealed that no significant difference in all the angular measurements of both skeletal and cranial bases existed between genders, while all linear and area measurements were usually higher in males than females and there was no significant difference in all the skeletal and cranial bases angles existed between different skeletal classes in both genders meaning that there is no relationship between cranial base flexure and skeletal classes. The angles N-S-Ar, N-S-Ba and SN-FH were always correlated negatively with both the angles SNA and SNB in all skeletal classes for both genders, while the angle SBa-FH showed weaker correlation with the angles SNA and SNB than the angle SN-FHin all skeletal classes for both genders. Conclusion: Cranial base flexure is not the main cause of skeletal malocclusions.